1990
DOI: 10.1590/s0036-46651990000200010
|View full text |Cite
|
Sign up to set email alerts
|

Serological studies on shistosomiasis mansoni in the Northeast Brasil

Abstract: Sera from the patients (N = 10) with schistosomiasis mansoni of the hospital of Federal University of Pernambuco, the Schistosoma mansoni egg-positive (N = 51) and -negative (N = 452) inhabitants in Cabo City area, out-patients (N = 37) of the IMIP hospital and Japanese immigrants (N = 127) in Petrolina City area of northeast Brazil as well as Japanese healthy subjects (N = 30) were examined by serological tests including an enzyme-linked immunosorbent assay with antigens prepared from eggs (ELISA-egg) and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…From March 2005, all HIV‐positive patients of sub‐Saharan African origin attending our department were tested for the presence of schistosomal antibodies in serum using an enzyme‐linked immunosorbent assay (ELISA), employing an unfractionated, water‐soluble extract of S. mansoni egg antigen (SEA/ELISA) [8,9] which detects immunoglobulin G antibodies to both S. mansoni and S. haematobium with high sensitivity and specificity and minimal cross‐reactivity to other helminths or internal parasites [10,11]. The method is currently used in all UK accredited clinical parasitology diagnostic laboratories (Clinical Pathology Association UK Accreditation) and has been validated against an indirect haemagglutination test using S. mansoni adult worm antigen (WA/IHA) [10] and against egg counts in an area of high endemicity [12].…”
Section: Methodsmentioning
confidence: 99%
“…From March 2005, all HIV‐positive patients of sub‐Saharan African origin attending our department were tested for the presence of schistosomal antibodies in serum using an enzyme‐linked immunosorbent assay (ELISA), employing an unfractionated, water‐soluble extract of S. mansoni egg antigen (SEA/ELISA) [8,9] which detects immunoglobulin G antibodies to both S. mansoni and S. haematobium with high sensitivity and specificity and minimal cross‐reactivity to other helminths or internal parasites [10,11]. The method is currently used in all UK accredited clinical parasitology diagnostic laboratories (Clinical Pathology Association UK Accreditation) and has been validated against an indirect haemagglutination test using S. mansoni adult worm antigen (WA/IHA) [10] and against egg counts in an area of high endemicity [12].…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that schistosomiasis mansoni is still endemic in the surrounding district. 28,29 Human serum samples. Serum samples were collected from 215 children (age range ‫ס‬ 1−17 years), after informed consent was obtained, for epidemiologic and clinical surveys on helminth infections.…”
Section: Methodsmentioning
confidence: 99%
“…Entretanto, sua utilização no nosso meio é ainda muito limitada, devido sobretudo à falta de reagentes comerciais aplicáveis ao diagnóstico da esquistossomose. Variantes técnicas têm sido empregadas para detecção de anticorpos contra antígenos de vermes adultos (Sathe et al, 1991;Silva et al, 1998;Valli et al, 1997) ou de ovos (Doenhoff et al, 1993;Eltiro et al, 1992;Kamal et al, 1994;Tanabe et al, 1990), de Schistosoma mansoni (Sambon, 1907). No entanto, alguns pesquisadores verificaram a presença de reações cruzadas em amostras de soro de indivíduos infestados com outros parasitas que não o S. mansoni, quando se utiliza extrato total como antígeno no método de ELISA e Western-blot para pesquisa de anticorpos IgG (Correia-Oliveira et al, 1988;Valli et al, 1997).…”
unclassified